A CASE STUDY ON THE CONSOLIDATION OF FINANCIAL STATEMENTS OF ENTITIES AFFILIATED THROUGH DIRECT CONSOLIDATION PROCEDURE - Deju, Mihai (Studies and Scientific Researches. Economics Edition, 2020)
The preparation of annual consolidated financial statements, in the context of the existence of group companies, represents a relatively new problematic issue for accounting practitioners, the world of the academia, as well as for the regulating bodies in the field of accounting. This situation generates intense debates among accounting specialists with the aim of finding practical solutions that facilitate the understanding and correct application of accounting regulations in the area of consolidating accounts. The present article approaches, by means of a case study, the specific aspects related to the consolidation of affiliated entities’ accounts by means of using the global integration method and the direct consolidation procedure.